ANALISIS PENGARUH FAKTOR - FAKTOR KEPUASAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA BIRO ADMINISTRASI PEMERINTAHAN SEKRETARIAT DAERAH PROVINSI JAWA TIMUR - Ramon Syahrial (Fakultas Ekonomi Universitas 45 Surabaya, 2014)
This study has aims to determine the effect of job satisfaction factors that comprising of compensation, career path, job variation, leadership attitude, and job environment on the job performance of officials and to determine the job satisfaction factors that have a dominant effect on official's job satisfaction and performance at Public Administration Bureau of District Secretariat of East Java Province. The populations in this study were all officials of Public Administration Bureau of District Secretariat of East Java Province and the determination of samples are taken with census method which amounted to 55 peoples. The variable in this study is Job Performance (Y), Job Satisfaction Factors (X), which are; Compensation (XI), Career (X2), Job Variations (X3), Leadership Attitude (X4) and Job Environment (X5). The analysis technique that used to analyze the data is multiple linear regressions. The results showed that the independent variables in this study, that are: compensation, career path, job variations and autonomy to act are simultaneously has effect on official's job satisfaction by 97.6%. Variables of compensation, career path, job variations and autonomy to act can explain variables of job satisfaction and there are effect between the two variables was tested. In partially, variable of compensation is the dominant variable than other independent variables toward variable of official's job satisfaction at Public Administration Bureau of District Secretariat of East Java Province